2019
DOI: 10.1302/0301-620x.101b2.bjj-2018-0340.r2
|View full text |Cite
|
Sign up to set email alerts
|

Trifocal versus bifocal bone transport in treatment of long segmental tibial bone defects

Abstract: Aims Many authors have reported a shorter treatment time when using trifocal bone transport (TFT) rather than bifocal bone transport (BFT) in the management of long segmental tibial bone defects. However, the difference in the incidence of additional procedures, the true complications, and the final results have not been investigated. Patients and Methods A total of 86 consecutive patients with a long tibial bone defect (≥ 8 cm), who were treated between January 2008 and January 2015, were retrospectively revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 24 publications
1
71
3
1
Order By: Relevance
“…Paley et al [21] stated that bone transport beneath the ap seemed to proceed more easily than in closed defects with scarred soft tissues and ap coverage may contribute to docking site union without grafting. The mean EFI in this series was 1.91 ± 0.3 months/cm, inferior to that reported by recent research studies on bone transport and ap technique [10,11]. In addition, this technique is only suitable for the cases with both ends with good soft-tissue coverage and without bone exposure after debridement.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Paley et al [21] stated that bone transport beneath the ap seemed to proceed more easily than in closed defects with scarred soft tissues and ap coverage may contribute to docking site union without grafting. The mean EFI in this series was 1.91 ± 0.3 months/cm, inferior to that reported by recent research studies on bone transport and ap technique [10,11]. In addition, this technique is only suitable for the cases with both ends with good soft-tissue coverage and without bone exposure after debridement.…”
Section: Discussioncontrasting
confidence: 82%
“…However, bifocal bone transport (BFT), which is regarded as a simple-level osteotomy bone transport, has the disadvantages of long frame duration, poor regenerates, and frequent complications. In recent decades, some scholars proposed the concept of TFT, which is also called double level osteotomy bone transport, and is strictly only suitable for bone defects over or equal to 8cm [10,11]. At present, there are few clinical reports about this technique.…”
Section: Introductionmentioning
confidence: 99%
“…Paley et al [19] stated that bone transport beneath the ap seemed to proceed more easily than in closed defects with scarred soft tissues and ap coverage may contribute to docking site union without grafting. The mean EFI in this series was 1.91 ± 0.3 months/cm, inferior to that reported by recent research studies on bone transport and ap technique [10,11]. In addition, this technique is only suitable for the cases with bilateral ends of the bone defects with good soft-tissue coverage and without bone exposure after debridement.…”
Section: Discussioncontrasting
confidence: 80%
“…An ideal osteotomy technique is one that minimizes soft tissue and periosteal disruption, lessens thermal necrosis, and produces high-quality healing tissue [1]. These goals can be accomplished with a technique that is truly minimally invasive and preserves the medullary, as well as periosteal blood supply [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, multiple drill-hole (MDH) and Gigli saw osteotomy are the two foremost methods for osteotomy, being favoured and recommended by many orthopedic surgeons [3][4][5][6]. Recently, several studies have evaluated their outcome and reported the best results for quality of the regenerated bone in comparison with other methods of osteotomy [2,7].…”
Section: Introductionmentioning
confidence: 99%